Desmoplastic nevus on giant nevus spilus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
Both very extensive congenital melanocytic nevi (CMN) with PAS > 20 cm (the size of a CMN is measured independently of age with PAS -predicted adult size - which is obtained by multiplying the maximum diameter at birth x3.3 for the lower limbs, x2.8 for the upper limbs and trunk, x1.7 for the head) and numerous CMN are the most common risk factor for neuro-cutaneous melanosis and prepubertal melanoma. A CMN with these characteristics should be monitored through inspection and palpation. The famous ABCDE rule in children is different from adults because the child’s melanoma (cM) is different from the adult: thus in the child remains in its original meaning only the E (Evolution) while A becomes Amelanotic because the cM is usually symmetrical and not pigmented; B becomes Bump and Bleeding because the borders of cM are usually regular, and it often occurs as a bleeding nodule; C becomes uniform Color because cM is most often monochromatic.